(untitled) (Journal of Scientific Research, 2012)
A total of 25 day old Cobb 500 broiler chicks were purchased and randomly divided into five groups (A, B, C, D and E). Group A served as noninfected, non-supplemented control. Group B were infected and non-supplemented while chicks of group C, D and E were supplemented oyster mushroom (Pleurotus ostreatus) @ 50, 100 and 150 mg/kg body weight respectively with feed from 2-28 day of age. The chicks of group B, C, D and E were challenged orally with 1 x 104 sporulated oocysts of Eimeria tenella on 10th day. The anticoccidial efficacy of oyster mushroom was evaluated based on oocysts counts per gram (OPG) of feces, weight gain, morbidity and mortality, necropsy findings and histopathology. Concerning the mean OPG count, body weight gain (p<0.01), morbidity and mortality the highest performance (p<0.01) was detected in group D and E on day 28 among the supplemented groups whereas group B showed the lowest performance. Group D and E showed the best results in regards of body weight, OPG counts, morbidity, mortality and post mortem findings as compared to healthy control (group A). So it could be concluded that supplementation of 100-150 mg oyster mushroom/kg body weight reduces the development of cecal coccidiosis in chicken. © 2013 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v5i1.12229 J. Sci. Res. 5 (1), 185-193 (2013)